Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21512/tw.v21i2.6797
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ad Content and Ad Lengthon Consumer Response towards Online Video Advertisement

Abstract: The research aimed to determine the moderating effect of advertisement (ad) length on the relationships between ad content and the intention of skipping, as well as ad irritation. Previous research has discussed the factors that affect customers' intention of skipping and ad irritation, centering around the duration of an ad, and whether the ad is skippable. However, no previous research had focused on the relationship between the intention of skipping and ad irritation that consumers experience. The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 49 publications
1
14
0
1
Order By: Relevance
“…Fifth, novel idea represents advertisements that contain witty ideas and novel techniques. Few researchers have found that witty ads affect viewers' attitudes toward advertisements [24,48,49]. The identified keywords are witty, novel, fun, ridiculous, and charm.…”
Section: Exploratory Studymentioning
confidence: 99%
“…Fifth, novel idea represents advertisements that contain witty ideas and novel techniques. Few researchers have found that witty ads affect viewers' attitudes toward advertisements [24,48,49]. The identified keywords are witty, novel, fun, ridiculous, and charm.…”
Section: Exploratory Studymentioning
confidence: 99%
“…Ad irritation refers to the extent to which a viewer perceives ad content and strategies as offensive and annoying [25]. Many studies have indicated that ad content (e.g., messy, untrue, and exaggerated), execution (e.g., goal interruption), and placement (e.g., appearing too frequently) can trigger viewers to perceive ad irritation [24][25][26][27][28]. These studies have pointed out that as long as viewers have a way to avoid ads (e.g., clicking skip-ad button), they will do so [22,23].…”
Section: Ad Irritation and Its Effect On Ad Avoidancementioning
confidence: 99%
“…Thus, it is important to make ads valuable to viewers and thereby lead them to feel that watching ads is not "a waste of time" [11,30]. This solution requires that ad content carefully match viewers' interests or values based on their viewing behaviors [25,31]. However, matching all viewers' interests and preferences is very difficult.…”
Section: Ad Irritation and Its Effect On Ad Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…The effects of advertising elements in social media, Facebook included, the intention to buy or click, and any other consumer actions that lead to a sale are a field that is studied well. The impact is found from the different ad elements, such as emotions evoking, especially positivity and humor (Taylor et al 2011;Wu et al 2018;Lee et al 2018), content informativeness level and type (Haj Eid et al 2020;Lutfie and Marcelino 2020), video ad length (Munsch 2021;Nettelhorst et al 2020;Raditya et al 2020), and content design (Al Kurdi and Alshurideh 2021;Xin Teo et al 2019). The importance in the same matters of information, entertaining content, advertising value, and being credible has also been confirmed by studies (Warsame et al 2021).…”
Section: Introductionmentioning
confidence: 99%